Child feeding and stunting prevalence in left-behind children: a descriptive analysis of data from a central and western Chinese population - Ban, Lu; Guo, Sufang; Scherpbier, Robert W.; Wang, Xiaoli; Zhou, Hong; Tata, Laila J. (Springer, 2016)
Objectives: To examine the effect of parental rural-to-urban internal migration on nutritional status of left-behind children and how this is related to guardianship. Methods: We used UNICEF China’s maternal and child health survey data to investigate stunting prevalence and feeding practices in children left behind by rural-to-urban internal migrant parents. We also assessed the effects of primary guardianship which is related closely with parental migration. Results: Of 6,136 children aged 0-3 years, over one third was left behind by one or both parents. About 13% were left behind by mothers, leaving guardianship primarily to grandmothers. Left-behind status was not associated with stunting, yet children who were cared for primarily by their fathers had a 32% increase of stunting compared to children cared for by the mothers (adjusted odds ratio[aOR]=1.32;95% confidence interval=1.04-1.67). Children with migrant mothers were less likely to receive age-appropriate breastfeeding (aOR=0.04;0.02-0.10) and a minimum acceptable diet (aOR=0.56;0.39-0.79) compared with non-left-behind children. Conclusions: Guardian’s feeding behaviours varied, and was inappropriate for both children affected and not affected by parent’s rural-to-urban internal migration. Community-based infant and young child feeding counselling and support should be provided to all caregivers.